Pengaruh Sistem Akuntansi Manajemen, Komitmen Organisasi, dan Motivasi Terhadap Kinerja Manajerial : Studi Kasus di Mangano Sushi Sukoharjo - Dwi Sulistanti (Jurnal Ilmiah Keuangan Akuntansi Bisnis, 2026)
This study aims to examine the influence of management accounting systems, organizational commitment, and work motivation on managerial performance at Mangano Sushi Sukoharjo. This study employed a quantitative approach with an explanatory research design. The population consisted of 60 employees, all of whom were selected using a census sampling technique. Primary data were collected through a structured questionnaire using a five-point Likert scale and analyzed using multiple linear regression after passing validity, reliability, and classical assumption tests. The findings reveal that management accounting systems and work motivation have a positive and significant effect on managerial performance, whereas organizational commitment does not significantly affect managerial performance. These findings indicate that the availability of relevant information to support managerial decision-making and employees' work motivation are associated with improved managerial performance. This study contributes empirical evidence to the management accounting literature from the perspective of Contingency Theory and provides practical implications for organizations in strengthening management accounting systems and enhancing employee motivation to improve managerial performance.